Associations between lifestyle risk, β‐amyloid, tau, and cognition in late mid‐life: Neuroimaging / Normal brain aging. (7th December 2020) - Cody, Karly Alex; Koscik, Rebecca L.; Erickson, Claire M; Birdsill, Alex C; Berman, Sara E; Chin, Nathaniel A.; Clark, Lindsay R; Christian, Bradley T; Betthauser, Tobey J; Johnson, Sterling C
Abstract: Background: Modifiable lifestyle risk (LR) factors are increasingly viewed as preventive strategies for AD and dementia; however, the impact of LR factors on AD biomarkers or AD biomarker‐related cognitive decline remains unknown. We utilized the Lifestyle for BRAin health (LIBRA) index 1)to investigate whether baseline LR predicts incident cognitive impairment and/or β‐amyloid onset; 2)to examine the effect of longitudinal LR on cognitive decline in the presence of β‐amyloid; 3)to preliminarily examine the cross‐sectional relationship between late‐midlife LR and β‐amyloid and tau biomarker groups. Method: Participants (n=1244, Table 1) from the Wisconsin Registry for Alzheimer's Prevention completed serial health and neuropsychological assessments with a subset undergoing PiB PET imaging (n=238) and MK‐6240 (n=186) PET imaging. Cox regressions assessed the predictive utility of baseline LIBRA for incident cognitive impairment (1.5 SD below covariate adjusted 3‐test Preclinical Alzheimer's Cognitive Composite, PACC‐3) and β‐amyloid duration (i.e. age at assessment – estimated age PiB(+)). Linear mixed models examined the main effects and age interactions of LIBRA and β‐amyloid duration on longitudinal cognitive performance. Group differences in LIBRA were assessed across biomarker groups, where amyloid (A+) and tau (T+) positivity were defined as a global PiB DVR>1.19 and entorhinal cortex MK‐6240 SUVR>1.27, respectively. Result: In the survival analysis, baseline LIBRA predicted risk for incident cognitive impairment of subjects unimpaired at baseline (HR=1.18; Figure 1). In the amyloid imaging subset, baseline LIBRA did not predict β‐amyloid onset (HR=0.85; Figure 1). Linear mixed effects models indicated a significant main effect of LIBRA (higher LIBRA risk = worse PACC‐3) and a significant interaction of β‐amyloid duration×age on PACC‐3 (longer β‐amyloid duration = faster PACC‐3 decline; Figure 2). In the combined imaging subset (n=186), there were no differences in LIBRA across biomarker groups (Kruskal‐Wallis H: 5.08, p=.166; Figure 3). Conclusion: These findings suggest that a healthy lifestyle is associated with overall cognitive performance but not the rate of cognitive decline or biomarker status. In this sample, LR did not influence the onset of β‐amyloid or hasten AD‐related cognitive decline. Replication of this finding and future work is necessary to better understand the relationships between LR factors, cognitive decline and AD.